Teaching English creatively - Cremin, Teresa 1959- (Learning to teach in the primary school series, 2023)
"This text encourages and enables teachers to adopt a more creative approach to the teaching of English in the primary school. Fully updated to reflect the changing UK curricula, the third edition of this popular text explores research-informed practice and offers new ideas to imaginatively engage readers, writers, speakers and listeners. Inspiring, accessible and connected to current challenges and new priorities in education, Teaching English Creatively puts contemporary and cutting-edge practice at the forefront and includes a wealth of innovative ideas to enrich English teaching"--